Erector Spinae Plane Block Versus Retrolaminar Block: A Magnetic Resonance Imaging and Anatomical Study - Adhikary, Sanjib Das; Bernard, Stephanie; Lopez, Hector; Chin, Ki Jinn (Regional anesthesia and pain medicine, 2018)
Background and ObjectivesThe erector spinae plane (ESP) and retrolaminar blocks are ultrasound-guided techniques for thoracoabdominal wall analgesia involving injection into the musculofascial plane between the paraspinal back muscles and underlying thoracic vertebrae. The ESP block targets the tips of the transverse processes, whereas the retrolaminar block targets the laminae. We investigated if there were differences in injectate spread between the 2 techniques that would have implications for their clinical effect.MethodsThe blocks were performed in 3 fresh cadavers. The ESP and retrolaminar blocks were performed on opposite sides of each cadaver at the T5 vertebral level. Twenty milliliters of a radiocontrast dye mixture was injected in each block, and injectate spread was assessed by magnetic resonance imaging and anatomical dissection.ResultsBoth blocks exhibited spread to the epidural and neural foraminal spaces over 2 to 5 levels. The ESP block produced additional spread to intercostal spaces over 5 to 9 levels and was associated with a greater extent of craniocaudal spread along the paraspinal muscles.ConclusionsThe clinical effect of ESP and retrolaminar blocks can be explained by epidural and neural foraminal spread of local anesthetic. The ESP block produces additional intercostal spread, which may contribute to more extensive analgesia. The implications of these cadaveric observations require confirmation in clinical studies.